Minimally Invasive Craniocervical Decompression for Chiari 1 Malformation: An Operative Technique - Quillo-Olvera, Javier; Navarro-Ramírez, Rodrigo; Quillo-Olvera, Diego; Quillo-Reséndiz, Javier; Kim, Jin-Sung (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Chiari malformation type 1 (CM-1) is an ectopia of the cerebellar tonsils below the foramen magnum that causes severe disability due to its neurologic symptoms. The treatment of choice for CM-1 is decompression of the craniovertebral junction (CVJ). In some patients only an extradural decompression by removing the atlanto-occipital ligament may be sufficient. In other patients, duraplasty is necessary. In this case, we report the operative technique used to treat a CM-1 in a 16-year-old male patient who presented with severe headache and gait instability. A micro-decompression of the suboccipital bone and posterior arch osteotomy of C1 through a 2-cm midline incision was performed under surgical microscope magnification. A duraplasty was performed through the same approach. The patient was discharged home after 2 days in the hospital and returned to regular activities at school 3 weeks after surgery. The minimally invasive technique presented here is a viable option for the posterior decompression of the CVJ in patients with CM-1 using a low-cost self-retaining retractor.
Keywords: Chiari malformation; decompression; atlanto-occipital; craniocervical junction; minimally invasive surgery